1981
DOI: 10.1016/0091-3057(81)90219-7
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned defensive burying: A new paradigm for the study of anxiolytic agents

Abstract: Behavioral paradigms that have been designed to mimic forms of learning that are important for the survival of animals in the wild, rather than to minimize the contributions of adaptive predispositions, may prove to be particularly useful for studying the behavioral effects of drugs. In the present experiments, the propensity of rats to bury sources of aversive stimulation was disrupted in a dose-dependent fashion by a single injection of the anxiolytic drug, diazepam. This suggested that the conditioned defen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
171
1

Year Published

1996
1996
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 389 publications
(183 citation statements)
references
References 30 publications
11
171
1
Order By: Relevance
“…The LC is a major target of CRF neurotransmission in the brain (Van Bockstaele et al 1996) and is positioned to influence the functioning of the entire nervous system though modulation of noradrenergic activity (Abercrombie and Jacobs In agreement with its attenuation of burying responses to CRF administration, DSP-4 pretreatment also decreased the duration of probe burying in the conditioned defensive burying test, which is considered a validated rat test of anxiety (Treit et al 1981). No differences in the latency to contact the probe were observed between DSP-4-treated and control animals, indicating that the attenuation of burying was not due to an overall decrease in locomotion or exploratory activity.…”
Section: Burying Behavior Is Mediated By Forebrain Nementioning
confidence: 96%
See 2 more Smart Citations
“…The LC is a major target of CRF neurotransmission in the brain (Van Bockstaele et al 1996) and is positioned to influence the functioning of the entire nervous system though modulation of noradrenergic activity (Abercrombie and Jacobs In agreement with its attenuation of burying responses to CRF administration, DSP-4 pretreatment also decreased the duration of probe burying in the conditioned defensive burying test, which is considered a validated rat test of anxiety (Treit et al 1981). No differences in the latency to contact the probe were observed between DSP-4-treated and control animals, indicating that the attenuation of burying was not due to an overall decrease in locomotion or exploratory activity.…”
Section: Burying Behavior Is Mediated By Forebrain Nementioning
confidence: 96%
“…This commonly-used behavioral test of anxiety measures burying behavior in rats that is directed towards an electrified probe (Treit et al 1981). As shown in Figure 7, DSP-4 pretreatment produced a significant decrease in time spent burying the shockprobe (t(17) = 2.77, p = 0.01).…”
Section: Effects Of Dsp-4 Lesions On Conditioned Shock-probe Buryingmentioning
confidence: 99%
See 1 more Smart Citation
“…Rodents will bury an electrified probe following conditioning in which they receive shocks from the probe 43 , and will even spontaneously bury novel marbles introduced into their home cages 44 . This burying behavior is quantifiable and sensitive to anxiolytics 45,46 . Hyponeophagia (novelty suppressed feeding) has also been used to assess anxiety-like behavior in rodents; in a novel environment, hungry mice exhibit an increased latency to feed that is sensitive to BZDs and SSRIs 47,48 .…”
Section: Measuring Anxiety-related Behaviors In Rodentsmentioning
confidence: 99%
“…In this test, rats shocked from a stationary, electrified probe push bedding material from the floor of the experimental chamber toward the shock-probe (ie they bury the probe), avoid further contacts with the probe, and exhibit freezing behavior (Treit et al, 1994(Treit et al, , 1981Frye and Seliga, 2003;Pinel and Treit, 1978). In rats it has been demonstrated that anxiolytic drugs such as diazepam decrease burying towards the shock-probe (de Boer et al, 1990;Treit et al, 1993;Tsuda et al, 1988), whereas anxiogenic drugs such as yohimbine increase shock-probe burying (Tsuda et al, 1988).…”
Section: Shock-probe Burying Testmentioning
confidence: 99%